Estudo fitoquímico de Palicourea officinalis e distribuição espacial dos metabólitos secundários das folhas de espécies de Psychotria e Palicourea por DESI-MS direto e indireto - Moraes, Aline Pereira (2017)
Palicourea and Psychotria (Rubiaceae) are known for the presence of compounds with potential biological activity, such as the indole alkaloids, flavonoids and norisoprenoids. In order to increase the chemical knowledge of Palicourea species, the phytochemical study of the aerial parts of Palicourea officinalis was carried out for the first time, through the isolation by chromatography and structural elucidation of the compounds by NMR and mass spectrometry. The following secondary metabolites were identified: the novel alkaloid 18-epi-brachycerine; the norisoprenoids: guettardionoside, 3-oxo--ionol 9-O--D-apiofuranosyl-(1®6)--D-glucopyranoside, vomifoliol 9-O--D - apiofuranosyl-(1®6)--D-glucopyranoside and 7,8-dihydro-vomifolol 9-O--D-apiofuranosyl-(1®6)--D-glucopyranoside; the lignan syringaresinol--D-glucoside; the pyrazines 2,5-deoxyfructosazine, 2,6-deoxyfructosazine and fructosazine; the flavonoids quercetin 3-O-sophoroside and kampferol 3-O-sophoroside; 3-caffeoyl and 4-caffeoylquinic acids; feruloylquinic acids; salicylic acid; coumarin scopoletin; besides ursolic and oleanolic triterpenes acids and glycosylated sitesterol and stigmasterol steroids. In addition, for the first time, the indirect and direct DESI-MSI techniques were applied in the study of the spatial distribution of alkaloids in the leaves of Palicourea coriacea and Psychotria prunifolia. The indirect approach was applied successfully and showed distinct distribution patterns of the alkaloids detected. The image data were confirmed by LC-MS.